Human Resources as Business Partners: A Bibliometric Journey Towards Strategic Human Resource Management - Loso Judijanto (West Science Social and Humanities Studies, 2025)
This study investigates the evolving role of human resource management (HRM) as a strategic partner within organizations through a bibliometric analysis. Using publications indexed in Scopus, this research maps the intellectual structure and thematic development of HRM in strategic contexts such as business processes, innovation, and sustainability. The findings highlight HRM’s growing alignment with organizational goals, fostering innovation and adaptability in response to global challenges. By analyzing citation patterns, co-authorship networks, and keyword co-occurrences, the study identifies key trends, influential scholars, and emerging themes, offering insights into how HRM has transformed from a transactional function to a strategic asset. This study contributes to both academic discourse and practical strategies by emphasizing HR’s critical role in achieving organizational success and long-term sustainability.